Identification of prognostic factors for chronicity in patients with low back pain: A review of screening instruments - Melloh, Markus; Elfering, A.; Egli Presland, C.; Roeder, C.; Barz, T.; Rolli Salathé, C.; Tamcan, O.; Mueller, U.; Theis, J. (2009)
Low back pain (LBP) is currently the most prevalent and costly musculoskeletal problem in modern societies. Screening instruments for the identification of prognostic factors in LBP may help to identify patients with an unfavourable outcome. In this systematic review screening instruments published between 1970 and 2007 were identified by a literature search. Nine different instruments were analysed and their different items grouped into ten structures. Finally, the predictive effectiveness of these structures was examined for the dependent variables including "work status", "functional limitation", and "pain". The strongest predictors for "work status" were psychosocial and occupational structures, whereas for "functional limitation" and "pain" psychological structures were dominating. Psychological and occupational factors show a high reliability for the prognosis of patients with LBP. Screening instruments for the identification of prognostic factors in patients with LBP should include these factors as a minimum core set. © 2008 Springer-Verlag.